Russian Resource Materials Guide - Seymour, Viveca; Hawaii State Dept. of Education, Honolulu. Office of Instructional Services ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
This guide provides the teacher of Russian with helpful background material and activities on the geography of the Soviet Union and the history of Russia as well as its customs, traditions, literary selections, songs, foods, and festivals. In addition to these topics, the introductory chapter outlines a philosophy for teaching and learning Russian language and culture, and program objectives. The final chapters list audiovisual resources, dictionaries, texts, and other resource materials. (AMH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Aids; Class Activities; Cultural Education; Educational Objectives; Elementary Secondary Education; Geography; History; Instructional Materials; Russian; Second Language Instruction; Slavic Languages; State Curriculum Guides; Teaching Guides; Guides, Classroom -- Teacher